Effect of digital chemotherapy extravasation education based on Orem’s self‐care theory in cancer patients: A quasi-experimental study - Hang Thi Nguyet Ho; Trang Thi Kieu Duong; Nguyet Thi Tran; Phuong Thi Anh Nguyen; Trang Thi Thuy Ho; Duc Nu Minh Ton (PLoS ONE, 2026)
Purpose Digital health education is crucial in preventing and managing chemotherapy extravasation among cancer patients. We aimed to evaluate the effectiveness of a digital chemotherapy extravasation educational intervention on knowledge, self-care abilities, and self-efficacy in cancer patients. Methods A quasi-experimental longitudinal design was conducted with 80 cancer patients at Hue University of Medicine and Pharmacy Hospital, Vietnam, from September 2022 to November 2023. The control group (n = 40) received routine health education on chemotherapy extravasation, while the experimental group (n = 40) participated in an extravasation education program based on Orem’s Self-Care Theory and utilized digital technology. This study assessed knowledge levels, self-care abilities, self-efficacy in preventing and managing chemotherapy extravasation, and the effectiveness of digital technology applications at three different time points. Chi-square tests, independent t-tests, and Analysis of Variance with Repeated Measures were employed to analyze the data. Results There were statistically significant differences in knowledge (F = 16.24, p < 0.001), self-care abilities (F = 35.37, p < 0.001), and self-efficacy (F = 46.27, p < 0.001) between the intervention and control groups over time, with the intervention group showing greater improvements across all outcomes. Qualitative findings revealed three key categories: moving forward to self-care readiness, promoting emotional resilience, and enhancing a positive care environment. Patients perceived the digital technology applications as highly effective, especially in terms of perceived usefulness and ease of use, and showed significant changes across time (F = 9.93, p < 0.001). Conclusion Digital chemotherapy extravasation education based on Orem’s Self-Care Theory offers an effective approach that enhances cancer patients’ knowledge while strengthening their self-care. Therefore, healthcare providers should integrate digital education into routine patient care to enhance self-efficacy, reduce complications, and support better treatment outcomes.